Aspek Transendental Raja’ Dalam Novel Berselimut Surban Cinta Karya Irwanto Al- Krienciehie: Tinjauan Sastra Profetik - Nia Wedia; Emil Septia; Armet (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
This research was conducted to determine the transcendental aspect of the king' in the novel Berselimut Surban Cinta by Irwanto al-Krienciehie through a review of prophetic literature. Novels that have religious value can be used to make people (readers) aware to always draw closer to God. The transcendental aspect of the king' describes a form of hope to the Creator. The purpose of this study is to describe the transcendental aspect of the king' in the novel Berselimut Surban Cinta. This type of research used qualitative research. The method used in this research is descriptive analysis method. The data in this study are in the form of words, sentences and discourses that describe the transcendental aspects of the king'. Based on the analysis of the research data it can be concluded that the transcendental aspect of the king' involves a hope, supplication or prayer to God. This hope in God is in the form of hoping for help, protection, healing or blessings in life. The transcendental aspect in the novel covered in turbans of love by Irwanto al-Krienciehie can be seen from the attitudes of the characters, such as always worshiping and always praying.